The importance of earthquake interactions for injection‐induced seismicity: Retrospective modeling of the Basel Enhanced Geothermal System. Issue 10 (27th May 2016) - Catalli, Flaminia; Rinaldi, Antonio P.; Gischig, Valentin; Nespoli, Massimo; Wiemer, Stefan
Abstract: We explore the role of earthquake interactions during an injection‐induced seismic sequence. We propose a model, which considers both a transient pressure and static stress redistribution due to event interactions as triggering mechanisms. By calibrating the model against observations at the Enhanced Geothermal System of Basel, Switzerland, we are able to reproduce the time behavior of the seismicity rate. We observe that considering earthquake interactions in the modeling leads to a larger number of expected seismic events (24% more) if compared to a pressure‐induced seismicity only. The increase of the number of events is particularly evident after the end of the injection. We conclude that implementing a model for estimating the static stress changes due to mutual event interactions increases significantly the understanding of the process and the behavior of induced seismicity. Key Points: We model synthetic catalogues for induced seismicity accounting for earthquake interactions in terms of static stress transfer Static stress interactions affect the number of seismic events, which increase (24% more) with respect to a pressure‐induced only case Static stress transfer has a significant role in understanding the rate and total number of events, as well as their spatial distribution